Computational Study of the Phytochemical Constituents from Uncaria tomentosa Stem Bark against SARS-CoV-2 Omicron Spike Protein. (14th May 2022) - Herrera-Calderon, Oscar; Saleh, Abdulrahman M.; Yepes-Perez, Andres F.; Aljarba, Nada H.; Alkahtani, Saad; Batiha, Gaber El-Saber; Hañari-Quispe, Renan Dilton; Chavez, Haydee; Pari-Olarte, Josefa Bertha; Loyola-Gonzales, Eddie; Almeida-Galindo, José Santiago; Kong-Chirinos, José Francisco; et al.
Abstract : The SARS-CoV-2 Omicron variant has spread rapidly and is considered the predominant variant in the world, and its main characteristic is related to evade immunity from natural infection or vaccines, due to its multiple mutations in the spike protein. On the other hand, medicinal plants have been used as alternatives therapies to ameliorate some signs and symptoms in COVID-19, and in our previous work, the cat's claw ( Uncaria tomentosa ) stem bark has been studied in vitro and showed antiviral activity on SARS-CoV-2 as well as in silico studies on the 3CL pro protein and as disruptor between the ACE-2 human receptor and the spike protein. The aim in this computational study was to determine the main phytochemical constituents from U. tomentosa stem bark against the SARS-CoV-2 Omicron spike protein based on molecular modeling. A molecular docking was carried out on the isolated phytochemicals in a previous work against the SARS-CoV-2 Omicron spike protein-binding domain (PDB ID: 7T9K). Next, a molecular dynamic study was carried out to monitor the stability during the MD simulations. As results proanthocyanidin-C1 (-10.76 kcal/mol), quinovic acid-type 2 (-9.86 kcal/mol), and proanthocyanidin-B2 (-9.82 kcal/mol) were the constituents with the best binding free energy on the SARS-CoV-2 Omicron spike protein, and the best compound was stable during the dynamic simulation under physiological conditions. It is concluded that the anthocyanidin-based compounds determined in the stem bark ethanol extract could be responsible for the potential antiviral activity on SARS-CoV-2 Omicron variant, and the proanthocyanidin-C1 emerged as a powerful candidate to combat new variants.